The Implementation of LAUDATO SI as the Embodiment of Integral Ecology in Atma Jaya Yogyakarta University - Susilawati, Marietta D.; Rhity, Hironimus; Malau , Sonang Rifaldi (Westscience Press, 2024)
The wrong paradigm towards self and others leads humans to individual pride and collective egoism. Technocratic and mechanical views can obscure human dignity, because humans are considered as objects and usability values only. Anthropocentric, mechanistic and technocratic paradigms make individuals alienated from others, both with each other, as well as with other creatures and entities. This research aims to explore the Encyclical Laudato Si and its implementation in Atma Jaya Yogyakarta University (UAJY). As a university, UAJY plays an important role in creating a catholic education that respects human dignity, the value of interconnectedness and builds an integral ecology. The results of the research are expected to be more effective in realising the encyclic in Atma Jaya Yogyakarta University. This research uses a qualitative method, and the approach used was a mixture of library research and field research. The material object of the research is policy, while the formal object is moral philosophy.